Interaction between barren-ground caribou and muskrats - Kelsall, John P. (Canadian Journal of Zoology, 1970)
Barren-ground caribou, Rangifer tarandus groenlandicus, have been observed to systematically expose, trample, and eat the pushups constructed on ice in winter by muskrats, Ondatra zibethicus, for feeding. Muskrats may be inconvenienced, or frozen out, by this behavior and the caribou may be attracted by the frozen but green vegetation of which the pushups are constructed.